Pilates as a method of improving physical fitness and strengthening the health of students assigned to a special medical group - Kadochnikova N.I.; Avdeeva M.S.; Kim T.K.; Alexandrova G.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is aimed at determining the impact of Pilates training on the level of physical development and physical fitness of students assigned to a special medical group. Methods and structure of the study.Thestudyinvolved48studentsaged18to20years.Theworkincludedmeasurementsandevaluation of anthropometricandfunctionalcharacteristics,aswell as an analysis of motivationalfactors. Results and conclusions. The results of the work carried out demonstrate that the inclusion of a set of Pilates exercises in the main part of the workout led to stabilization of body fat and water mass, increased muscle mass, improved flexibility of the spine and optimized the work of the cardiovascular and respiratory systems. In addition, students reported an improvement in their general condition and increased resistance to physical exertion, which had a positive effect on motivation to engage in physical education, attendance, and completing independent assignments in the subject of Physical Education.